Evacuation Route Determination in Indoor Architectural Environments Based on Dynamic Fire Risk Assessment - Jiaojiao Bai; Xikui Lv; Liangtao Nie; Mingjing Fang (Buildings)
The enclosed nature of indoor building spaces during fires creates complex fire environments and restricted evacuation routes, substantially elevating the risk of mass casualties. Traditional static evacuation routes not only overlook the complexity of fire scenarios but also fail to satisfy safety requirements for evacuation. To address this issue, this study proposes an enhanced A* algorithm to determine evacuation paths based on dynamic fire risk assessment. A dynamic fire risk assessment model is established using key fire environment parameters (e.g., temperature, visibility, and toxic gas concentration) and their corresponding personnel harm thresholds. This model quantifies fire risks within a discrete space. The A* algorithm is improved by integrating fire risk values and initial direction constraints into its heuristic function and path update strategy, thereby increasing the algorithm’s accuracy and efficiency. Using a subway station fire as a case study, the simulation results indicate that the improved algorithm can update evacuation paths in line with the dynamic evolution of fire risks. It also identifies evacuation routes by balancing fire risk, distance, and initial direction. This approach maintains the original path direction while substantially reducing path risk, achieving an approximate 70% reduction in individual evacuation path risk. This method can guide building fire safety design and the formulation of emergency evacuation plans. It also serves as a reference for path guidance during emergencies.